Preparedness of Youth in Facing Menarche in the Era of the Industrial Revolution 4.0 - Tina Farida; Yuni Puji Widiastuti; Siti Musyarofah (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Adolescence is a transition from puberty to adulthood. This period, there will be many changes either physical, psychological, or social that teenagers will experience one of them is Menarche. Mental readiness is urgently needed in the face of menarche due to anxiety and fear of appearing, and indispensable knowledge of self-care during menstruation. The purpose of this research is to know the characteristics and readiness of adolescents in the face of menarche in the era of industrial revolution 4.0. The type of research method used is descriptive survey. The population in this study was 45 pegandon junior high school students. Proportional sampling technique. Data analysis is done with statistics deskriftiv. The results of the student readiness study with less than 75.6%, and the readiness category in the good category as much as 24.4% of respondents. It is expected that health officials will further improve the implementation of health promotion activities especially in adolescents about the onses of menstruation so that teenagers are better prepared in the face of menarche.